Simulation of the behaviour of CNC machine-tools in three-axis milling of sculptured surfaces. (25th October 2010) - Pessoles, Xavier; Landon, Yann; Mousseigne, Michel; Rubio, Walter
Three-axis high-speed machining (HSM) of sculptured surfaces is currently programmed with linear or B-spline interpolation using CAM software. In both cases, due to axis dynamic limits of the CNC machine-tools, the desired feed rate is rarely reached, leading to lower productivity and impaired quality. In order to allow an optimisation of the process, a simulator is proposed in this paper. Changes in position, velocity, acceleration and jerk of each axis during three-axis HSM operations are modelled, based on a trapezoidal acceleration scheme. The relative speed between tool and workpiece is then computed for linear segments as for B-spline paths. Transitions between segments are also simulated. The three-axis simulator is experimentally validated through machining of a turbine blade.